2009
DOI: 10.1111/j.1749-5687.2008.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Security Beyond the State: Global Security Assemblages in International Politics

Abstract: To date, most discussion of security privatization in international politics has been focused on the role of private military companies and mercenaries. This article seeks to shift the focus away from the battlefields and toward the less spectacular privatization and globalization of commercial private security. Drawing on Saskia Sassen's notion of state ''disassembly,'' we situate the growth of private security within broader shifts in global governance. Pointing to the weakness of seeing the rise of private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
158
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(192 citation statements)
references
References 29 publications
2
158
1
8
Order By: Relevance
“…1 As a consequence, representatives of public security agencies in several Western countries have started to increasingly call upon private companies to participate in the management of various national security issues, with an overall political aim of considerably reducing security risk and making the entire society more resilient and resistant to all kinds of threats, natural disasters and man-made catastrophes [21,23,[33][34][35]. According to the former US Secretary of Homeland Security Janet Napolitano, for example, Bhomeland security … requires not just a 'whole of government', but a 'whole of nation' approach.…”
Section: What Is Outsourced To Private Companies Beyond Pmscs?mentioning
confidence: 99%
See 3 more Smart Citations
“…1 As a consequence, representatives of public security agencies in several Western countries have started to increasingly call upon private companies to participate in the management of various national security issues, with an overall political aim of considerably reducing security risk and making the entire society more resilient and resistant to all kinds of threats, natural disasters and man-made catastrophes [21,23,[33][34][35]. According to the former US Secretary of Homeland Security Janet Napolitano, for example, Bhomeland security … requires not just a 'whole of government', but a 'whole of nation' approach.…”
Section: What Is Outsourced To Private Companies Beyond Pmscs?mentioning
confidence: 99%
“…Building on Foucault's notion of space, 2 2). Similarly, Parker and Taylor suggested that we are witnessing the emergence of Ba new security paradigm in which financial borders and parameters are best understood as a 'complex assemblage' in which private financial institutions are in effect, authorized to make security decisions^( [7], 953, also see [1,2]). …”
Section: New Security Arrangements and Their Conceptualizations Beyonmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this development has not been reflected in a larger academic literature, except in one of its aspects: the growing global market in (in)security. Studies on this market have convincingly shown how security has increasingly been commoditized and privatized by security companies, mercenaries or 'corporate warriors' (Abrahamsen and Williams 2011;Avant 2005;Krahmann 2010;O'Reilly 2010;Singer 2003). O'Reilly (2010) is among the authors who trace this 'statecorporate symbiosis' around security provision back to the 1970s and the corporate sector, specifically the extractive industries.…”
Section: Contemporary Risk Management: the Backgroundmentioning
confidence: 99%